Moderation of Islamic Family Law in Southeast Asia - Siregar, Sampurna (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
This study aims to analyze the moderation of Islamic Family Law in Southeast Asia, focusing on how sharia principles are aligned with the social, cultural, and legal dynamics in the region. This study also aims to explore the efforts of countries such as Indonesia, Malaysia, and Brunei in adapting Islamic family law to remain relevant to local contexts and existing social development trends. The method used in this study is a qualitative approach with literature study, which involves analysis of various written sources, including laws and regulations, legal documents, and case studies from each country. The results of the study show that the moderation of Islamic family law in Southeast Asia includes efforts to integrate the principles of justice, human rights, and gender equality in the implementation of sharia law. In Indonesia, the implementation of the Compilation of Islamic Law (KHI) reflects efforts to protect the rights of women and children, while in Malaysia, sharia courts play a role in balancing sharia values with the needs of contemporary society. The study found that despite the challenges in harmonization between Islamic law and national law, a moderation approach allows Islamic family law to remain relevant and responsive to social change without sacrificing the basic principles of sharia